Fiscal policy developments in india ,1947 to 2007 - Sury, M.M. (New Delhi, 2007)
Fiscal policy is an important instrument of the general economic policy of a government. It is concerned with the use of a government's taxation and expenditure powers to influence economic activities in an economy at the aggregate level. It also deals with financial relations between different tiers of government in a federal polity. Through the medium of budget, fiscal policy determines the level of taxation, public expenditure, borrowings, and the issuing of additional currency by a government. In India, the external payments crisis of 1991 - which led to the initiation of economic reforms - was the result of a deteriorating fiscal situation during the latter half of 1980s. Fiscal imbalance was identified as the underlying cause of the twin problems of inflation and the difficult balance of payments position. This book provides an exhaustive and analytical account of fiscal developments in India since Independence (1947) with focus on post-1991 reforms. It examines many aspects of India's fiscal policy including government budgeting, the tax system, public expenditure, public debt, fiscal federalism, and the functional responsibilities and sources of revenue of local bodies.
Keywords: Fiscal policy-India-1947 to 2007